Prolonging the lives of buried crude-oil and natural-gas pipelines by cathodic protection - Lilly, M. T.; Ihekwoaba, S. C.; Ogaji, Stephen O. T.; Probert, Sydney D. (Elsevier, 2007)
In Nigeria, a major problem is the corrosion of the external surfaces of such pipelines, which are not usually adequately safeguarded during construction. A cathodic protection system should be applied to the pipeline before this period.
Keywords: Corrosion; Buried pipes; Cathodic protection; Impressed-current; Sacrificial-anode